2012
DOI: 10.1504/ijhfe.2012.052009
|View full text |Cite
|
Sign up to set email alerts
|

New organisational issues and macroergonomics: integrating management systems

Abstract: Integration and embedding interrelated concepts has become a major research field crossing over several scientific areas. Benchmarking, globalisation, sustainable development, clouding information flows, flexible work arrangements, democracy in management and teammanship over leadership are, currently, widely discussed issues among the industrial and academic communities. Systems integration has been reported in several technical areas, namely, in sensor development (organic-inorganic), artificial human tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The development of an IMS was focused as a research topic by several authors adopting case studies as research methods and addressing companies operating in disparate activity sectors such as those conducted by Brendler and Brandli (2011) in an apparel company, Giacomello et al (2014) and Masood et al (2014) in building companies, Rotaru et al (2005) in the food industry, Lobonţ and Pascu (2012) in higher education institutions, Marques et al (2014) in a waste treatment facility, Mehrabi et al (2013) in a power management company, Satolo et al (2013) in a Brazilian sugar and ethanol manufacturing unit, Walker and McAleer (2014) in a council’s waste management service, von Ahsen (2014) in the automotive industry, López-Fresno (2010) in the airline industry, Khanna et al (2010) in Indian organizations, Bernardo et al (2016) in Greek companies and Vitoreli and Carpinetti (2013) in multiple companies. Amid the studied features, the main motivations (Domingues et al , 2011a, 2014; Simon et al , 2012), drawbacks (Domingues et al , 2012, 2014; Simon et al , 2014b), expected benefits (Bernardo et al , 2015; Carvalho et al , 2015; Zeng et al , 2011), critical success factors (Domingues et al , 2011b; Sampaio et al , 2012), the integration strategies (Bernardo et al , 2011; Ivanova et al , 2014; Karapetrovic, 2002), the integration levels (Abad et al , 2014; Jørgensen et al , 2006), models (Bernardo, 2014; El Idrissi et al , 2014; Olaru, Maier, Nicoarǎ and Maier, 2014; Rebelo et al , 2014) and the extension to other sector specific requirements (Roessler et al , 2014) were widely reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of an IMS was focused as a research topic by several authors adopting case studies as research methods and addressing companies operating in disparate activity sectors such as those conducted by Brendler and Brandli (2011) in an apparel company, Giacomello et al (2014) and Masood et al (2014) in building companies, Rotaru et al (2005) in the food industry, Lobonţ and Pascu (2012) in higher education institutions, Marques et al (2014) in a waste treatment facility, Mehrabi et al (2013) in a power management company, Satolo et al (2013) in a Brazilian sugar and ethanol manufacturing unit, Walker and McAleer (2014) in a council’s waste management service, von Ahsen (2014) in the automotive industry, López-Fresno (2010) in the airline industry, Khanna et al (2010) in Indian organizations, Bernardo et al (2016) in Greek companies and Vitoreli and Carpinetti (2013) in multiple companies. Amid the studied features, the main motivations (Domingues et al , 2011a, 2014; Simon et al , 2012), drawbacks (Domingues et al , 2012, 2014; Simon et al , 2014b), expected benefits (Bernardo et al , 2015; Carvalho et al , 2015; Zeng et al , 2011), critical success factors (Domingues et al , 2011b; Sampaio et al , 2012), the integration strategies (Bernardo et al , 2011; Ivanova et al , 2014; Karapetrovic, 2002), the integration levels (Abad et al , 2014; Jørgensen et al , 2006), models (Bernardo, 2014; El Idrissi et al , 2014; Olaru, Maier, Nicoarǎ and Maier, 2014; Rebelo et al , 2014) and the extension to other sector specific requirements (Roessler et al , 2014) were widely reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, organisations have sought to identify and develop management systems that provide an adequate cost-benefit relationship and, at the same time, a prominent position in the market in which they operate, enhancing, among others, costs and losses reduction during the production process (Domingues, Sampaio, & Arezes, 2012;Hoyle, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With separate and sometimes incompatible management subsystems, organisations incur significant costs, increase in errors and failures, efforts duplication, unnecessary bureaucracy and excessive documentation. These issues have a very significant negative impact on stakeholders, mainly employees and customers (Beckmerhagen, Berg, Karapetrovic, & Willborn, 2003;Domingues et al, 2012;Sampaio, Saraiva, & Domingues, 2012). According to Asif, Fisscher, Bruijn, and Pagell (2010) the strategy should be the integration of those standards in a holistic system, so that organisations could manage their operations through a single management system (Rasmussen & Jørgensen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The recurring themes addressed in the mainstream literature within the IMSs scientific domain reported the limitations of the lack of integration (Almeida et al , 2014; Domingues et al , 2012, 2015), enabled the identification of critical success factors (Almeida et al , 2014; Oliveira, 2013) and dissected the guidelines and strategies for integration of MSs (Oliveira, 2013; Rebelo et al , 2014a). In addition, several authors proposed some contributions on the proper design of IMSs (Garengo and Biazzo, 2013; Manzanera et al , 2014; Rebelo et al , 2014b; Zeng et al , 2007), on the factors that impact the integration level attained (Bernardo et al , 2011, 2012) and suggested integration levels or degrees (Bernardo et al , 2009; Jørgensen et al , 2006; Jørgensen, 2008; Sampaio et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%